2010
DOI: 10.1038/npre.2010.4336.1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and nanostructural mechanisms of deformation, strength and toughness of spider silk fibrils

Abstract: Spider silk is one of the strongest, most extensible and toughest biological materials known, exceeding the properties of many engineered materials including steel. Silks feature a hierarchical architecture where highly organized, densely H-bonded beta-sheet nanocrystals are arranged within a semi-amorphous protein matrix consisting of 31-helices and beta-turn protein structures. By using a bottom-up molecular-based mesoscale model that bridges the scales from Angstroms to hundreds of nanometers, here we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 0 publications
4
63
0
1
Order By: Relevance
“…These results can be compared with our previous results, which applied constant force and velocity according to different bending directions [30,31]. Furthermore, the results can also be compared with spider silk, which is mainly composed of rich β strands with various crystal areas [39,40]. Although different loading conditions have been applied in this study to compare our results to previous studies, we observed the similar fracture toughness of polymorphic hIAPP fibrils.…”
Section: Elastic Properties and Plastic Behavior Of Hiapp Fibrilssupporting
confidence: 71%
“…These results can be compared with our previous results, which applied constant force and velocity according to different bending directions [30,31]. Furthermore, the results can also be compared with spider silk, which is mainly composed of rich β strands with various crystal areas [39,40]. Although different loading conditions have been applied in this study to compare our results to previous studies, we observed the similar fracture toughness of polymorphic hIAPP fibrils.…”
Section: Elastic Properties and Plastic Behavior Of Hiapp Fibrilssupporting
confidence: 71%
“…The length of the polyalanine motifs is not only optimized with respect to the secondary structure that they adopt but also optimized with respect to the size of the β-sheet nanocrystals of the fiber, since the mechanical properties of the Ma thread decrease as the crystal size increases. 51 The spacer region of MiSp1 probably contains some α-helix segments. Finally, Cyl and Ac proteins are predicted to adopt significant amounts of α-helices.…”
Section: Discussionmentioning
confidence: 99%
“…Such an interpretation is also supported by more recent molecular dynamics simulations on b-sheet structures in silk and their contribution towards mechanical properties (Nova et al, 2010).…”
Section: Discussionmentioning
confidence: 58%